Organization factors influencing nurse ability to prevent and detect adverse drug events in public hospitals using a patient safety model - Ali Azeez Al-Jumaili; Sarah K. Abbood; Ashwaq N. Abbas; Hind Mowafak Rafaeel; Fatima Raheem Mohammed; AL-Zahraa Ali (Elsevier, 2021)
The objective of this study was to measure organization factors that can influence the ability of nursing staff to prevent and detect ADEs in public hospitals using Systems Engineering Initiative for Patient Safety (SEIPS) model. Methods: This was a multi-center cross-sectional study. The study included a self-administered paper-based survey which was distributed and collected between October through December 2019. The study participants were nurses from 11 public hospitals located in two Iraqi provinces. Binary logistic regression was used to measure the relationship between the independent SEIPS factors (persons, organizations, tools, tasks, and environments) and the incidence of ADEs (outcome variable). Results: The study recruited 603 nurses (68.3% men) from 11 public hospitals across two provinces. Less than half (48.8%) of the nurses received enough training to detect ADEs, 43.1% had adequate experience to detect ADEs, and 69.8% had to report ADEs in a special record. More than three-quarters (78.4%) believed that their jobs need fast work. Two of the five SEIPS model domains had significant negative association with the incidence of ADEs including organization (nurse-physician collaboration) and nurse experience in ADE detection. Conclusions: Nursing staff face several challenges to prevent and minimize ADEs including shortages in nurses, inadequate nurse experience in ADE detection, no training for ADE detection was received, fear of reporting ADEs, and a lack in monitoring equipment. Increasing nurse/patient ratio and providing more monitoring equipment and training courses can minimize ADEs and enhance their detection.